2017
DOI: 10.4269/ajtmh.17-0109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Seroprevalence of Trypanosoma cruzi Infection in a Military Population in Texas

Abstract: Abstract.Recent biosurveillance findings at Joint Base San Antonio (JBSA), a large military installation located in south-central Texas, indicate the potential for vector-borne human Chagas disease. A cross-sectional study was conducted to determine the prevalence and seroprevalence of Trypanosoma cruzi infection in highest risk subpopulations on the installation, including students and instructors who work and sleep in triatomine-endemic field settings. Real-time polymerase chain reaction, enzyme-linked immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…cruzi transmission during training or patrolling in endemic areas, has been proposed as an activity that allows improving the surveillance strategies that protect humans and canines belonging to military forces in endemic areas of T . cruzi [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…cruzi transmission during training or patrolling in endemic areas, has been proposed as an activity that allows improving the surveillance strategies that protect humans and canines belonging to military forces in endemic areas of T . cruzi [30, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Surveillance of CD with the military first came about as a result of multiple military working dogs (MWDs) requiring medical attention attributable to cardiomyopathy, later diagnosed as CD. A study was then conducted to assess seroprevalance in MWDs, which was 8% among the MWDs housed and trained at Joint Base San Antonio (JBSA-Lackland) in San Antonio, Texas [72,73]. Unpublished data from another study conducted on the same military base found that 57% (n = 75) of 131 triatomines collected were T. cruzi-positive, with 33% (n = 25) testing positive for human blood [74].…”
Section: Impact On a Texas Us Military Installationmentioning
confidence: 99%
“…Additionally, this information also prompted an ongoing voluntary screening study at JBSA-Lackland to test basic military trainees (BMTs) at the beginning and end of their training sessions at the installation. This screening program, however, was implemented after protective measures were put into place, and there have not been any cases of transmission occurring on JBSA-Lackland to date [73]. It has been recommended that additional vector surveillance and testing for CD be conducted on military training installations throughout the southern USA in an effort to surveil training environments that may present hazardous exposure to our military populations.…”
Section: Impact On a Texas Us Military Installationmentioning
confidence: 99%
“…This species infected by T. cruzi has been collected inside domestic areas, as well as in piles of granitic rocks in the cape region of Baja California Sur State, Mexico (Jiménez and Palacios , Jiménez et al , Astorga et al ). The World Health Organization (), as well as the United States Army (Webber et al ) considered that travellers are at risk of exposure to blood‐sucking bugs when trekking, camping, or using poor‐quality accommodation. Dipetalogaster maximus is an aggressive triatomine and commonly leaves its shelter when hungry, even in daylight, to get a blood meal that includes human blood.…”
Section: Introductionmentioning
confidence: 99%